Impact of agricultural practices on animal biodiversity (Zoological Records and Reviews, 2024)
Agricultural intensification remains the dominant driver of animal biodiversity loss in European farmland landscapes, yetthe relative importance of specific management practices -- pesticide application, fertilisation intensity, tillage regime,crop diversity, and structural element retention -- varies among taxa and regions. This study quantifies the independentand combined effects of six agricultural practice parameters on four animal groups (carabid beetles, breeding birds, small mammals, and farmland butterflies) across 96 paired conventional and agri-environment scheme (AES) farm plots in Spain, the Netherlands, and Austria (n = 22,847 individual records across 318 taxa, 2021-2023). Pesticide applicationindex (PAI) was the strongest negative predictor of carabid beetle diversity (GLMM beta = -0.62 +- 0.09, p < 0.001) andbutterfly richness (beta = -0.54 +- 0.08, p < 0.001). Fertilisation intensity (nitrogen application > 120 kg N/ha/yr)significantly reduced sward structural complexity, indirectly suppressing breeding bird diversity by 28.4 +- 5.8%(mediation analysis; p < 0.001). Crop diversity (Shannon index of crop types within 500 m) was the strongest positivepredictor of breeding bird richness (beta = +0.48 +- 0.08, p < 0.001). AES plots with wildflower margins, reduced tillage,and pesticide restrictions supported 42.4 +- 6.8% higher mean species richness than adjacent conventional plots acrossall four animal groups. The biodiversity benefit of AES was significantly moderated by landscape context: AES plotsembedded in low-diversity landscapes (< 20% semi-natural habitat within 2 km) showed 64.8% lower biodiversity benefitthan those in heterogeneous landscapes. These findings provide an empirical basis for optimising CAP Eco-schemedesign to maximise biodiversity outcomes per unit programme expenditure.